Biosurfactants as promising multifunctional agent: A mini review - Akbari, Sweeta; Nour, A. H.; R. M., Yunus; Farhan, Abdulrahman Hasan (IJIRSS, 2018)
Biosurfactants are derived from plants and microorganisms such as fungi, yeast, and bacteria. Biosurfactants are also called natural surfactants which are amphiphilic biological compounds comprised of both hydrophilic and hydrophobic moieties. The environmental concerns about the effect of toxic and conventional surfactants have increased the demand for renewable and biodegradable surfactants with low toxicity and other useful effects. Therefore, the application of biosurfactants has gained much attention in different industries mainly in petroleum, food, cosmetic and pharmaceutical products. This review summarizes the utilization of biosurfactants as emulsifying, wetting, foaming and antimicrobial agents in various industrial processes along with their promising availability and ensuring environmental quality.